Dynamics of Anti-Terrorism Regulation: A Comparative Study Between Indonesia, Malaysia and the United States: Dinamika Regulasi Anti-Terorisme: Studi Perbandingan Antara Indonesia, Malaysia, dan Amerika Serikat - Anang Hendri Prayogo; Geofani Milthree Saragih; Erdianto Effendi; Andi Hakim Lubis; Yuliana Yuliana (Indonesian Journal of Counter Terrorism and National Security, 2025)
This paper examines the dynamics of anti-terrorism regulations in Indonesia, Malaysia and the United States by comparing the legal frameworks and law enforcement mechanisms in each country. legal frameworks and law enforcement mechanisms that apply in each country. The purpose of this research is to analyse how each country shapes its anti-terrorism law as a response to national threats, while at the same time maintaining a balance of as a response to national threats, while at the same time maintaining the balance between state security and human rights protection. The main issues discussed include differences in legal approach, scope of state authority in counter-terrorism operations, as well as monitoring mechanism to prevent authority in counter-terrorism operations, as well as monitoring mechanism to prevent abuse of authority. abuse of authority. The method used is juridical method used is normative-comparative juridical by analysing statutory instruments, government policies, and institutional practices in the three countries. The results The results show that Indonesia emphasises procedural guarantees in its anti-terrorism law, Malaysia maintains a preventive detention model rooted in historical security doctrine. rooted in historical security doctrine, while the United States applies a layered a layered approach backed by extensive intelligence powers and judicial oversight. judicial oversight. In conclusion, although all three countries prioritise national security, their approaches reflect different security, their approaches reflect different legal traditions and political contexts. political context. Therefore, a balanced regulatory model should take into account effectiveness, constitutional accountability and protection of fundamental rights.